KNOWLEDGE, ATTITUDE AND SERVICE QUALITY AGAINST BEHAVIOR USING PUBLIC TRANSPORTATION (International Conference on Social and Islamic Studies, 2022)
The research examines and analyzes the lack of public behavior in using public transportation in Makassar City.The research aims to identify and analyze knowledge, attitudes, and quality of service on behavior using public transportation. The research uses a qualitative descriptive approach located at the city service center. Total sample of 150 respondents using stepwise analysis method. The results showed that people's behavior using public transportation was at a moderate level, the average knowledge was in the moderate category, while the average attitude and quality of service was in the low category. Service quality was the dominant factor influencing behavior in using public transportation.